PENERAPAN ASAS PARI PASSU PRO RATA PARTE TERHADAP PEMBERESAN HARTA PAILIT PT DHIVA INTER SARANA DAN RICHARD SETIAWAN (STUDI KASUS PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR: 169 PK/PDT.SUS-PAILIT/2017) - Monitacia Kamahayani; Suyud Margono (Jurnal Hukum Adigama, 2020)
One of the main purpose of bankruptcy law is made to ensure division of bankruptcy property from debtor to the creditors that suitable with pari passu pro rata parte principle which means split the bankruptcy property to unsecured creditors based on the consideration how many invoice from those creditors. Inside the verdict of the Indonesia supreme court number: 169 PK/PDT.SUS-PAILIT/2017 we all can saw the division of bankruptcy property PT Dhiva Inter Sarana and Richard Setiawan that have been divided by curator that shown some inequity to one of the unsecured creditors specifically to PT Bank Maybank Indonesia, Tbk (before PT Bank Internasional Indonesia, Tbk), feels some inequity to the list of division bankruptcy property remembering that PT Bank Maybank Indonesia, Tbk (before PT Bank Internasional Indonesia, Tbk) provide funds to PT Dhiva Inter Sarana and Richard Setiawan to bought a land and built a house in Tangerang therefore they do legal effort in cassation and judicial review but in the end the supreme court judges refuse with the final provision. Just like a scale that used as a symbol of justice the judges in supreme court must think about the ease in this case the division of bankruptcy property so that the unsecured creditor can have the right to claim in accordance with the definition and application of pari passu pro rata parte principle.